Upaya Manajemen Stratejik Terhadap Kualitas Pelayanan Konser Blackpink World Tour (Born Pink) Di GBK - Dian Sudiantini; Novia Rahmawati; Niken Salsabilla; Nendy Yuliarrani (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
Various types of music that exist today, one of which is Korean pop (k-pop), adds color to the world of music and entertainment. One of the most famous music groups from South Korea itself, namely blackpink, in early 2023 has held a world tour concert (born pink) at GBK. The fans were very enthusiastic to watch the concert, especially the blinks who don't only live in JABODETABEK, but also from outside JABODETABEK. The Blackpink concert which was held for two days fulfilled trends on various social media, not only happiness but also other judgments from the audience which made the audience uncomfortable with the concert. So this study aims to evaluate, analyze, and examine strategic management efforts on the service quality of the Blackpink world tour (born pink) concert at GBK. The data were collected directly from the respondents, the tools used in the research were through questionnaires and using SPSS data processing. The results of this study are proven by that strategic management has a significant effect on service quality.